Two Applications of Soil Water Balance in Unsaturated Pyroclastic Soils. (2016) - Pirone, Marianna; Rianna, Guido; Reder, Alfredo; Pagano, Luca; Urciuoli, Gianfranco
Abstract: Evaluation of the monthly soil water balance (SWB) provides a tool for understanding and predicting the effects of seasonal and long-term changes in soil water conditions within many geotechnical problems. In this paper, two applications of the SWB approach in the pyroclastic partially saturated soils are shown. Firstly, rainfall, evapotranspiration, water storage measured or estimated at the experimental site in Monteforte Irpino (in Southern Italy) are shown. Secondly, rainfall, infiltration, actual evapotranspiration and water storage measured by data provided by a physical model are shown. In the both cases, data are reported over two years (2010-2012). The physical model was constituted by a wooden tank filled with reconstituted silty pyroclastic soil taken from experimental site at Monteforte Irpino (AV) and it was exposed to the atmosphere at a site in Napoli. Comparison between soil hydraulic behaviours observed is discussed and the scale effects on the estimation of the SWB are analysed, treating with practical implications. From the results, it is clear that similar trends in SWB and the same value of suction over wet season (10 kPa) can be observed at both the scales in spite of differences in meteorological conditions and hydraulic properties of soils exposed to atmosphere.